Working Principle of Contactor in Electrical System - Deitje Sofie Pongoh; Muhammad Arif Kurniawan Prajitno; Mutiara Gissyella Kalalo; Imanuel Rakwer Orlando Kraar; Eadvent Supit Jearty Mokalu (Publikasi Indonesia, 2025)
Contactors are important components in electrical systems that function as electromagnetic switches to control electric current in various places, both in industry and in housing. The working principle of the contactor is based on the electromagnetic field that occurs when the coil gets electricity, so that the contacts can be open or closed control the flow of electricity. So that it can control high currents, so when the contactor is given a voltage or electricity, it will produce an electromagnetic field to attract the main contact so that the voltage or electricity is connected, and vice versa when the voltage for the contactor is removed, the magnetic field will disappear and the main contact will return to its normal position. Contactors are often used in controlling electric motors, lighting systems, and industrial automation. This journal explains the working principle, as well as the main role of contactors in electrical systems. A good understanding of contactors can help in the design and maintenance of electrical installations to make them safer and more efficient in the industrial world.